Local municipalities and the influence of national networks on city climate governance: Small places with big possibilities - Coulombe, Cynthia; Maya-Drysdale, David; McCormick, Kes (Frontiers in Sustainable Cities, 2022)
Reaching the 1.5°C target of the Paris Agreement not only requires ambitious goals from national governments, but also the active participation of local municipalities. It is in cities where climate actions need to be implemented to reduce greenhouse gas emissions and reach international and national climate goals. While the importance of cities and their participation in networks has been well researched, studies have systematically neglected the committed individual agents in small and medium-sized cities and overlooked the importance of national networks. To address these research gaps, this article looks at how local climate managers use their municipality’s membership in national networks to increase action and implementation. This article is based on twelve semi-structured interviews with seven municipal representatives and five representatives of two national city networks, and four informal discussions. Through comparative content analysis, it was identified that the main functions derived from network participation are direct exchanges between the climate managers, mobilization of others in the municipality, accounting of greenhouse gas emissions, and project support. These functions helped overcome key limitations that the actors often faced within the municipality related to a lack of legal competences, administrative resources and internal support for climate work and financial resources. This has implications for city networks which have been focusing on larger cities and not including smaller cities who have less capacity and who can benefit the most from the functions provided by them.